Accumulation, transport and potential treatment of surface sediment on car parks with channel drains - Barlow, James Vincent (Cranfield University, 2015)
Urban pollutants have been identified as a significant source of environmental pollution, posing a risk to human health, the environment, and are toxic to flora and fauna. Highways are recognised as one of the key sources of pollution, from both vehicles, and surrounding infrastructure. A number of studies have investigated accumulation of sediment and the associated pollutants on highways, and the runoff generated as a result of rainfall. Car parks share many potential contributory sources of pollutants with highways, but there is a lack of studies regarding car parks, despite them being identified as a significant percentage of urban land use. A series of experiments were undertaken in order to develop an understanding of the characteristics of car park sediment. The physical and chemical characteristics of sediment were analysed at different stages throughout the drainage system. Firstly on the sediment accumulated on car park surfaces, followed by that mobilised and transported into a channel drain during simulated rainfall events. Finally, potential treatment of pollutants within sediment in a channel was quantified. The physical and chemical characteristics of car park sediment was shown to be similar during both the accumulation (build-up) and wash-off stages, suggesting that the accumulated sediment is generally mobilised and transported to the channel drain (wash-off). Furthermore, both the physical and chemical characteristics of the sediment were shown to be similar to those found on highways, thorough the build-up and wash-off phases. Finally, potential treatment of organic pollutants (PAH) by biodegradation was demonstrated, but not comprehensively proved.
Keywords: Urban Pollution; Wash-off; Runoff; Particulate Matter; Heavy Metals; PAH; SUDS